Disordered Eating, Menstrual Irregularity, and Musculoskeletal Injury in High School Athletes: A Comparison of Oral Contraceptive Pill Users and Nonusers - Thein-Nissenbaum, Jill M. (SAGE Publications, 2014)
BACKGROUND: The female athlete triad is the interrelatedness of energy availability, menstrual function, and bone density. Currently, limited information about triad components and their relationship to musculoskeletal injury in the high school population exists. In addition, no study has specifically examined triad components and injury rate in high school oral contraceptive pill (OCP) users. HYPOTHESIS: To compare the prevalence of disordered eating (DE), menstrual irregularity (MI), and musculoskeletal injury (INJ) among high school female athletes in OCP users and non-OCP users. STUDY DESIGN: Retrospective cohort study. LEVEL OF EVIDENCE: Level 2. METHODS: The subject sample completed the Eating Disorder Examination-Questionnaire (EDE-Q) and Healthy Wisconsin High School Female Athletes Survey (HWHSFAS). Athletes were classified by OCP use and sport type. RESULTS: Of the participants, 14.8% reported OCP use. There was no difference in MI and INJ among groups. The prevalence of DE was significantly higher among OCP users as compared with non-OCP users; OCP users were twice as likely to meet the criteria for DE (odds ratio [OR], 2.47; 95% confidence interval [CI], 1.20-5.09). OCP users were over 5 times more likely to have a global score that met criteria for DE as compared with non-OCP users (OR, 5.36; 95% CI, 1.92-14.89). CONCLUSION: Although MI and INJ rates are similar among groups, there is a higher prevalence of DE among high school female athletes using OCPs as compared with non-OCP users. CLINICAL RELEVANCE: Because OCP users may be menstruating, clinicians may fail to recognize the other triad components. However, DE exists in the menstruating OCP user. As such, clinicians should be vigilant when screening for triad components in high school OCP users, particularly DE.